2004
DOI: 10.1074/jbc.m405377200
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP A1 and the SR Proteins ASF/SF2 and SC35 Have Antagonistic Functions in Splicing of β-Tropomyosin Exon 6B

Abstract: Mutually exclusive splicing of exons 6A and 6B from the chicken ␤-tropomyosin gene involves numerous regulatory sequences. Previously, we identified a G-rich intronic sequence (S3) downstream of exon 6B. This element consists of six G-rich motifs, mutations of which abolish splicing of exon 6B. In this paper, we investigated the cellular factors that bind to this G-rich element. By using RNA affinity chromatography, we identified heterogeneous nuclear ribonucleoprotein (hnRNP) A1, the SR proteins ASF/SF2 and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 57 publications
2
68
0
Order By: Relevance
“…Computational analyses indicate that sequence motifs for ESEs are more frequent in exons than in introns (28). However, there are a number of examples in which SR protein binding sites are located within the intron and can function to promote splicing of upstream 5Ј splice sites (8,(29)(30)(31)(32). At the same time, negative intronic regulatory elements with which SR proteins interact have also been found (20,29,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Computational analyses indicate that sequence motifs for ESEs are more frequent in exons than in introns (28). However, there are a number of examples in which SR protein binding sites are located within the intron and can function to promote splicing of upstream 5Ј splice sites (8,(29)(30)(31)(32). At the same time, negative intronic regulatory elements with which SR proteins interact have also been found (20,29,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…This reiteration is suggestive of cooperative protein binding within a flank. Some of these particular sequences resemble binding sites of known factors, e.g., CTCTCT in clcn7-3 has been seen in core polypyrimidine-binding proteinbinding sites (Southby et al 1999;Carstens et al 2000), AGGG in thbs4-12 is part of several hnRNP A1-binding sites (Burd and Dreyfuss 1994;Boerkoel et al 1995;Abdul-Manan et al 1996;Expert-Bezancon et al 2004), GGGA in thbs4-12 is the core element of the hnRNP H family (Caputi and Zahler 2001) and sequences bearing G-triplets can potentially bind U1 snRNP (McCullough and Berget 2000). We also compared the effect of flank deletions on winner content and phenotype.…”
Section: The Experimentally Tested Exons Contain Hgc and Lgc Winning mentioning
confidence: 99%
“…The balance between these has been shown to control many genes, reviewed in (House and Lynch 2008). Changes in the levels of the splicing factors in various B cell types (Bruce, Dingle et al 2003) and during development have been shown to alter splicing patterns (Expert-Bezancon, Sureau et al 2004). For, example, SRp20 plays an important role in alternative splicing of the ED1 exon (de la Mata and Kornblihtt 2006).…”
Section: Splicing Of Igh Rna Is Altered In Plasma Cellsmentioning
confidence: 99%